Immune Boosting Drugs -A Myth or Reality - A Review - Allour Vaishnavi1, Anitha Roy2 , A.K.Anjali3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The concept of boosting immunity was a popular one. Although the lay public is exposed to information onhow to boost immunity and the only evidence-based approach to this is vaccination. The aim of this reviewwas to analyze such immune boosters as a myth or reality and the information about immune-boostingdrugs available on the Internet. Of the 30 approaches to boost immunity recorded, the top ones were diet(76%), fruit (70%), vitamins (65%), antioxidants (54%), probiotics (52%), minerals (49%), and vitamin C(56%). Interestingly, vaccines ranked 27th, with only 12% mentioning them. Commercial websites are animportant component of the information available to the public on the topic and thus contribute to providinginformation that is biased. Vaccines have developed society by saving lives and dramatically reducing theburden of infectious disease. Most successful vaccines have been developed empirically, but recent advancesin immunology are beginning to shed new light on the mechanisms of vaccine-mediated protection and thedevelopment of long-term immunity. The role of vaccination is to generate long term protection againstdiseases. Prime-boost vaccine strategies could improve cellular and also humoral immunity in severalanimal models, among various vaccine modalities. Although natural infection will often provide lifelongimmunity, current vaccinations need a booster dose to achieve durable protective humoral immune responses,regardless of whether the vaccine is based on infection with replicating live-attenuated vaccine strains of thespecific pathogen or whether they are derived from immunization with inactivated, non-replicating vaccinesor subunit vaccines. This review discusses the recent advances in immunization and the immune boostersand decides whether these are a myth or reality.